Manfaat Pembangunan Ekonomi Desa Wisata Puri Mataram Kampung Folry Sleman - Dony Kalmas; Rifki Khoirudin (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2020)
Puri mataram is a tourist destination located in the village of Tridadi, Sleman and was officially opened on November 1, 2018. Puri mataram was established by BUMDes Tridadi Makmur with financial assistance from the government and local residents. Funds used to build this tourist village amounted to Rp. 5.1 billion, of which 51% comes from villages. Managers also come from local residents. This 4.5 ha tourism destination has the cultural theme of the kingdom of Mataram, tourists can also enjoy traditional nuances with thick cultural values.In this study an analysis of benefits and costs arising from the development project Puri Mataram Tourism Village. The method used is a financial feasibility study by calculating the value of NPV, IRR, and Payback Period, and the method of comparison between benefits and costs, namely Benefit Cost Ratio. This study compares the benefits and costs for 12 years with a Discount Rate of 12.97%.From this study the NPV value of Rp. 2,180,078,195, an IRR value of 24%, a Payback Period with a payback period of 6 years 1 month, and a BCR value generated of 1.19 which as a whole has fulfilled business feasibility.